Musculoskeletal ultrasound may narrow the gap between patients and physicians in the assessment of rheumatoid arthritis disease activity. (28th April 2022) - Floris, Alberto; Rozza, Davide; Zanetti, Anna; Carrara, Greta; Bellis, Emanuela; Cauli, Alberto; Iagnocco, Annamaria; Scirè, Carlo Alberto; Piga, Matteo; ,
Abstract: Objectives: To investigate the association between patient–physician discordance in the assessment of disease activity and residual US synovitis/tenosynovitis in a cohort of patients with RA in clinical remission. Methods: A post hoc analysis of the STARTER study, promoted by the Musculoskeletal-US (MSUS) Study Group of the Italian Society for Rheumatology, was performed using data from 361 consecutive patients with RA in clinical remission. The global assessment of disease activity by each patient (PGA) and evaluator/physician (EGA) was recorded on a 100-mm visual analogue scale. The PGA-EGA discordance was classified as positive (PGA>EGA) or negative (PGA<EGA) using a cut-off of ±10 mm. The association of discordance with greyscale (GS) and power Doppler (PD) synovitis (S) and tenosynovitis (T) scores was evaluated through logistic regression analysis. The odds ratio for each point of the scores, adjusted for prespecified confounders (adjOR), was calculated. Results: The mean (s .d .) PGA and EGA scores were 6.1 (7.1) and 8.8 (12) mm, respectively, with a median (IQR) absolute difference of 4 (0–10) mm. Positive and negative discordances were recorded in 39 (10.8%) and 65(18.0%) patients, respectively. The GS-S (adjOR 1.099) and PD-S (adjOR 1.167) scores were associated with positive discordance ( P < 0.01), while the GS-T (adjOR 1.083), GS-S (adjOR 1.063) and PD-S (adjOR 1.089) scores were associated with negative discordance ( P < 0.05). The PGA-EGA discordance did not predict flares at 6 and 12 months. Conclusions: Patient–physician discordance is associated with the lack of US remission in patients with RA and may represent a further indication for MSUS.